Correlation of Clinical and Dosimetric Parameters With Radiographic Lung Injury Following Stereotactic Body Radiotherapy. (August 2015) - Kishan, Amar U.; Wang, Pin-Chieh; Sheng, Ke; Yu, Victoria; Ruan, Dan; Cao, Minsong; Tenn, Stephen; Low, Daniel A.; Lee, Percy
Radiographic changes occur in over half of patients treated with stereotactic body radiotherapy (SBRT) to the lung, correlating histopathologically with injury. We quantified radiographic density changes (ie, fibrosis) at 3, 6, and 12 months and investigated the relationship between these volumes and clinical and dosimetric parameters. The study population consisted of patients treated with SBRT to the lung for stage I primary lung cancers (n = 39) or oligometastatic lesions (n = 17). Fractionation schemes included 3 fractions of 12, 14, or 18 gray (Gy) and 4 fractions of 12 or 12.5 Gy prescribed to cover 95% of the planning target volume (PTV). Planning computed tomography (CT) scans were rigidly registered to follow-up CT scans obtained at intervals of 3, 6, and 12 months. Fibrotic volumes were contoured on the follow-up scans. Associations between the volume of fibrosis and clinical and dosimetric parameters were investigated using univariate linear regression. Scans were available for 65 and 47 lesions at 6 and 12 months, respectively. Age, years since quitting smoking, and GOLD Global Initiative for Chronic Obstructive Lung Disease score were significantly associated with increasing volume of fibrosis ( P < .05). Total dose, dose per fraction, PTV, and volumetric parameters (V0-V55) were also significantly associated with increasing volumes of fibrosis ( P < .01). For dosimetric parameters, the effect was largest for V55. Age, significant smoking history, and GOLD score were significantly associated with increasing volumes of fibrosis following SBRT. In a multivariate model adjusted for age and smoking history, V10 through V50 and PTV size remained significant predictors of fibrotic volume. Further, there is a strong dose–response relationship between the volume of lung exposed to a certain dose and the fibrotic volume. The predominant kinetic patterns of fibrosis demonstrate peaking fibrotic volumes at 6 and 12 months. These results provide insight for expectations of fibrosis after SBRT.